Risk in Malaysian Agriculture: The Need for A Strategic Approach and A Policy Refocus - Okezie Chukwukere Austin; Amir Hussin Baharuddin (Kajian Malaysia, 2012)
The agricultural sector is exposed to a variety of risks that occur with high frequency. These risks include climate and weather, natural catastrophes, pests and diseases, which combine to cause highly variable production outcomes. The broad objective of this study is to examine these agricultural risk factors and the policies in place for countering them. The approach adopted here includes an indepth review of literature, government policy documents and Emergency Disasters Databases (EM-DAT) data on disaster occurrences. Inferential statistics were employed in data analysis. Risk management in agriculture ranges from informal practices such as the avoidance of highly risky crops and crop and income-source diversification to formal measures such as crop insurance, a minimum-support price system and a futures market. Statistics show the prevalence of weather-related hazards of cyclone, floods, landslides, earthquake and tsunami. As to the impact of such hazards on human health, statistics for 1980–2010 show that deaths caused by epidemics amounted to 43.4% of all deaths arising from natural disasters. Epidemics accounted for the highest number of deaths against 5.8% the lowest arising from mass movement (dry). Government policy documents show that efforts have been made to manage hazards, such as the construction of the Stormwater Management and Road Tunnel (SMART), the tsunami-recovery plan and the December 2006 floodrecovery plan, among others. Analysis shows, however, that not every economic sector has a specific policy for addressing the effect of global warming on its productivity. The nation urgently needs to strengthen its ability to predict the effects of climate variability and subsequent weather hazards. This study recommends the establishment of a coordination-and-planning committee at the national level to address issues related to climate variability and climate change and to identify and mobilise the national capacity to strengthen research-anddevelopment activities in line with national priorities and needs.